2013
DOI: 10.1007/s00240-013-0616-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison one-step procedure with two-step procedure in percutaneous nephrolithotomy

Abstract: The aim of this study was to compare the effects of one-step percutaneous nephrolithotomy (PCNL) by the urologist alone and two-step PCNL by cooperating with the radiologist. We included 168 patients who underwent surgery by the same surgeon, 83 who underwent two-step PCNL, in which percutaneous nephrostomy insertion was performed by the radiologists on the day before endo-surgery, and 85 who underwent one-step PCNL, which involved the creation of a nephrostomy tract and performing the PCNL at the same time in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The authors interpreted this as the use of antibiotics appropriate to the culture obtained from the preoperative nephrostomy (5). In contrast, in the study by Chen et al, the presence of preoperative PCN did not significantly contribute to a reduction in operative time (6).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The authors interpreted this as the use of antibiotics appropriate to the culture obtained from the preoperative nephrostomy (5). In contrast, in the study by Chen et al, the presence of preoperative PCN did not significantly contribute to a reduction in operative time (6).…”
Section: Discussionmentioning
confidence: 92%
“…There are studies in the literature comparing data from patients who had a PCN catheter placed prior to PNL surgery with patients who had renal access during surgery. The availability of a PCN catheter preoperatively may have some advantages, but it may not always be possible to use this tract for renal access (4)(5)(6). A limited number of studies have investigated the availability of renal access in patients with previous PCN catheter placement in emergency situations (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…It is recommended that a standard channel for PCNL is established through the "two-step method", but there are disadvantages to this strategy [31].To overcome these shortcomings and reduce complications, urological surgeons frequently use a modi ed method, such as one-shot dilation and serial dilation [32].Moreover, Manuel et al reported that ultrasonography-guided dilatation can be safely performed with a high puncture accuracy and low bleeding risk [33]. In our previous study, we found that MARS signi cantly reduce bleeding compared to ultrasound-guided direct puncture, and here we also found that the accuracy of puncture method was a signi cant independent predictor of bleed during or following PCNL as previous studies mentioned [34].…”
Section: Discussionmentioning
confidence: 99%